Legal Education on the TPKS Act (Criminal Acts of Sexual Violence) and the Establishment of Village-Based Community Complaint Centers - Jayanti Puspitaningrum; Najamuddin Gani; Anwar Anwar; Abdul Rahman Upara; Zonita Zirhani Rumalean (PT. AVID MEDIA INDONESIA, 2026)
Sexual violence remains a persistent structural problem in Indonesian society, and rural communities in particular suffer from low legal literacy and limited access to formal complaint mechanisms. The enactment of Law Number 12 of 2022 on the Crime of Sexual Violence (UU TPKS) marked a paradigm shift by placing prevention, victim protection, and community participation at the center of the national legal framework. Yet the effectiveness of this law depends on how far its norms are translated into practice at the village level, where legal education is often sporadic and complaint channels remain distant from ordinary citizens. This article examines the urgency of continuous legal education on the TPKS Act and explores the establishment of village-based community complaint centers as an institutional bridge between normative protection and practical accessibility. Employing normative juridical research with statutory and conceptual approaches, the study analyzes the TPKS Act, the Village Law, and their implementing regulations alongside recent socio-legal literature. The findings show that community complaint centers, when embedded in sustained legal education and linked to formal referral pathways such as UPTD PPA, can strengthen early detection, reporting, and victim assistance. The article recommends a collaborative model integrating village government, community-based service providers, and law enforcement to operationalize the participatory mandate of the TPKS Act.